A Comparative Analysis of How Pakistani and American Print Media Construct Environmental Disaster Through Systemic Functional Linguistics - Mehr un Nisa; Dr. Muralitharan Doraisamy Pillai; Dr. Gulzar Ahmad; Shehzad, Yasir (ACADEMIA International Journal for Social Sciences, 2025)
This study investigates the way how Pakistani and American newspapers construct fundamentally different realities of the 2022 Pakistan floods through grammatical choices. The analysis is carried out by utilizing the well-known Systemic Functional Grammar. The study analyzed almost 327 clauses from two representative texts. One from Pakistan's newspaper ‘Express Tribune’ and the other one from America's newspaper ‘Wall Street Journal’. The research unveils certain crucial patterns in how linguistic tactics and resources actively shape the understanding of climate vulnerability, agency, and also the responsibility. On one hand, the text taken from Pakistani newspaper predominantly uses the relational and mental processes (62.7%), constructing floods as the problems which require democratic accountability and systemic analysis. On the other hand, the American newspaper text privileges the material processes (48.3%) which as a result position natural forces as autonomous agents acting upon the helpless peoples. On the basis of the systematic analysis of transitivity patterns, modality distributions, and thematic structures, the study shows how these grammatical choices generate what Halliday calls as "metafunctional harmony" which refers to the so-called coherent but contrasting worldviews about climate disaster. From one perspective, the interrogative mood, inclusive pronouns, and abstract themes in the Pakistani texts produce participatory discourse that positions readers as agents of change. From the other perspective, the American text's declarative mood, distancing pronouns, and concrete themes produce narrative immediacy that may generate sympathy but potentially obscures the systemic causation. These findings disclose the idea that the climate vulnerability is not merely just materially experienced, but they are also grammatically constructed and with profound implications for international climate cooperation and justice for the affected ones. This analysis contributes methodologically by developing a thematic grouping approach that reveals how grammatical patterns cluster meaningfully around different semantic domains.